A study on fatigue life of RC bridge and its improvement methods - B, Neha; S, Sruthy; T.M, Rahul (International Journal of Engineering and Technology, 2018)
Fatigue is a crucial factor which affects the total life and serviceability of highway bridges. There are several factors that contribute to the development of fatigue in RC bridges. Among them, traffic loads, wind loads and corrosion of reinforcement are some of the important factors to name a few. In order to address these fatigue issues and improve the fatigue life of highway bridges, many improvement meth- ods have been suggested in the literature. This study attempts to investigate the effectiveness of various improvement methods suggested in the literature. The improvement methods that has been included in this study are externally bonded reinforcement and deck overlay. To accomplish the objective, an existing highway bridge was selected based on the structural details and traffic data and then various improvement methods were applied to analyze its improvement in fatigue life. For analysis, an embedded reinforcement modeling was carried out in ANSYS followed by a nonlinear analysis in ANSYS workbench. The results of the study were found to be in alignment with AASTHO LRFD (2007), IRC SP 60(2002), IRC 6 (2014), IRC SP 37 (2010) and IRC 37 (2012) codal provisions. Â